Removal of H2S from Biogas Using Thiobacillus sp.: Batch and Continuous Studies - R. Shet and S. Mutnuri (Nature Environment and Pollution Technology, 2023)
Anaerobic digestion produces biogas which usually contains 60-70% of methane (CH4), 30-40% of carbon-di-oxide (CO2), and 10-2,000 ppm hydrogen sulfide (H2S). The concentration of H2S depends upon the type of substrate. H2S tends to corrode pipes and machines carrying them. The high concentrations of H2S present in biogas may adversely affect electricity generation. Hence, the removal of H2S and enrichment of biogas with CH4 is an essential step towards higher energy production. In the present study, the biological method of removing H2S using Thiobacillus sp. was demonstrated for a one cu.m anaerobic co-digestion (ACD) unit running on an organic fraction of municipal solid waste (OFMSW) and septage sludge. Initial lab scale studies were conducted by collecting the biogas generated from 1 cu.m digesters, and continuous experiments were optimized for the process parameters such as flow rate, the volume of medium with culture, time, the height of the column, column composition, etc. The raw biogas was purged in a liquid medium (LM) with a culture containing Thiobacillus sp. The studies with the LM containing Thiobacillus sp. culture showed a 68% removal of H2S in the first 8 min, and the saturation occurred at 75 min when the time-dependent experiment was studied. The smaller flow rate (0.48 L.min-1) and highest volume of culture (500 mL) showed better results than other parameters. The highest and average oxidation rates of sulfate were recorded as 39 and 40.3 ppm.sec-1, respectively, for 0.48 L.min-1 flow rate and 500 mL of the culture volume. In the column studies, a column containing cocopeat (CP) was studied for its efficiency in removing H2S. At a flow rate of 0.9 L.min-1, 25% adsorption was encountered and reached saturation at 90 min. The bed height of 9 inches with CP and plastic support (PS) showed a 20% H2S removal. The filling ratio of CP and PS (1:1) was the best ratio for proper gas passage with optimal time for adsorption/absorption. The kinetic, isotherm, and continuous models helped to understand the capacity of the adsorbent. Freundlich, Yoon-Nelson, and BDST model were best fit for the present study. A pilot scale setup for one cu.m biogas reactor showed an average of 50% removal of H2S for LM with culture, and an additional 20% removal was possible by the introduction of a column along with the liquid bed in series. An overall efficiency of 70-75% of H2S removal was achieved. No significant CH4 loss was encountered during the study.